Performance Analysis of Sustainable Agrotourism in Lebakmuncang Village - Ulya Rahmah; Endah Djuwendah (Journal of Business on Hospitality and Tourism, 2021)
Agro-tourism in Lebakmuncang Village has a selling value in the form of natural potential, agriculture, arts, crafts, and traditional culinary processing typical of the village. This agro-tourism has the potential of a sustainable tourism object. The purpose of this research is to measure the performance of agro-tourism from the perspective of naturalness, uniqueness, workforce involvement, land-use optimization, area arrangement, and education. The research design used is descriptive quantitative with a survey method. Collecting data using observation, questionnaires, interviews, and literature studies. The research data were analyzed using descriptive analysis with a Likert scale. The results showed that agro-tourism performance on naturalness was in the very good category. Meanwhile, the performance of agro-tourism towards uniqueness, the involvement of labor, optimization of land use, zoning, and education are categorized as good.